Accounting for previous performance of students by means of growth curves analyses to estimate the size, stability, and consistency of school effects. Issue 5 (18th August 2017) - Timmermans, Anneke; van der Werf, Greetje
ABSTRACT: The current study explored the size, stability, and consistency of school effects, using 2 effectiveness indicators: achievements of students at the end of primary school and growth in achievement across 3 years of schooling. The sample consisted of the scores of 25, 269 students on 3 subjects, taken in Grades 4 to 6 among 3 cohorts in 319 primary schools. The results showed that (a) for students' growth of achievement the relative proportion of variance at the school level seemed larger compared to achievement at the end of primary school; (b) the total variance in growth was substantially smaller compared to variance in achievement at the end of primary school; (c) school effects for growth are less stable across different cohorts than school effects established at a particular moment; and (d) school effects for growth are less consistent across multiple subject domains than school effects as indicated by students' achievement at a particular moment.